Effect of Le Fort I Maxillary Repositioning on Three-Dimensional Nasal Tip Rotation: A Comparative Study with Implication for the Asian Nose. Issue 4 (April 2021) - Denadai, Rafael; Chou, Pang-Yun; Yao, Chuan-Fong; Chen, Ying-An; Lin, Yi-Yu; Huang, Chiung-Shing; Lo, Lun-Jou; Chen, Yu-Ray
Abstract : Background: Le Fort I maxillary repositioning influences nasal morphology. In Asian cultures, upward nasal tip rotation with increased nostril exposure is considered aesthetically unpleasant and can have psychosocial consequences. This three-dimensional imaging–based study evaluated the effect of different Le Fort I maxillary movements on nasal tip rotation. Methods: Consecutive patients who underwent two-jaw orthognathic surgery ( n = 107) were enrolled. To achieve a standard head orientation, preoperative and 1-week and 12-month postoperative cone-beam computed tomography–derived three-dimensional craniofacial models were superimposed. Tip rotation angle was calculated according to the Frankfort horizontal plane for all three-dimensional digital models. The final tip rotation angle change was defined as 12-month postoperative value minus preoperative value. Translational maxillary movement types (advancement versus setback and intrusion versus extrusion), postoperative maxillary segment locations (anterosuperior, anteroinferior, posterosuperior, or posteroinferior), and actual linear maxillary changes were noted. Results: Advancement (1.79 ± 5.20 degrees) and intrusion (2.23 ± 4.96 degrees) movements demonstrated significantly larger final tip rotation angle changes than setback (−0.88 ± 5.15 degrees) and extrusion (0.09 ± 5.44 degrees) movements (all p < 0.05). Postoperative anterosuperior location (2.95 ± 4.52 degrees) of the maxillary segment demonstrated a significantly larger final tip rotation angle change than anteroinferior (0.48 ± 5.65 degrees), posterosuperior (−1.08 ± 4.77 degrees), and posteroinferior (−0.64 ± 5.80 degrees) locations (all p < 0.05). Translational maxillary movement and actual linear maxillary change were not correlated with final tip rotation angle change. Conclusion: Effects of Le Fort I maxillary repositioning on nasal tip rotation depend on movement types and maxillary segment location. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.